Role of the Legal Consultant as Related Party in Trade at the Capital Market - Sitepu, Febri Inggrit Tresia Br; Hutagalung, Tita Losary; Leonard, Tommy (Legal Standing : Jurnal Ilmu Hukum, 2020)
The capital market has an important role, because the capital market is one alternativeto collect funds from the public. In the capital market there is an expert in his field whois able to rule the capital market in the field of law is a Legal Consultant. The LegalConsultant has the duty to conduct legal examination and provide legal opinions aimedat assisting the company in realizing the public offering process. In accordance withapplicable norms. This paper will provide an explanation and understanding of the roleof a Legal Consultant in capital market activities. Because 3 legal consultants have highintegrity and are very trusted in carrying out legal checks and providing legal opinionsdirectly in accordance with the rule of law.